PEMETAAN FISIK LINGKUNGAN TAMBANG, DAMPAK DAN POTENSI YANG DAPAT DIKEMBANGKAN - Irvani Irvani; Fitri Ramdhani Harahap; Sujadmi Sujadmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2015)
Hundreds of years of tin mining on Bangka Island has caused damage to tens of thousands of hectares of land. Through the Kuliah Kerja Nyata Pemberdayaan Pemberdayaan Masyarakat (KKN-PPM), physical mapping of environmental damage due to mining and the potential that can be developed in Lumut Village, Riding Panjang and Gn. Muda village, Belinyu sub-district, Bangka district. Physical mapping was conducted through field observations of the mining area, focus group discussions (FGDs) and socialization of the potential of the pit. More than 3,000 ha of land is critical land, environmental damage resulting in erosion, sedimentation, flooding, drought and potential landslides. The pit has the potential to be developed as a source of clean water, fish farming and pit tourism. Generally, the community utilizes the pit as a source of clean water during the dry season. A total of 40 out of 128 collars have the potential to be developed as a source of clean water, a location for freshwater fish farming and the development of collector tourism.